Electron transport and visible light absorption in a plasmonic photocatalyst based on strontium niobate - Wan, D. Y. (2018)
Semiconductor compounds are widely used for photocatalytic hydrogen production applications, where photogenerated electron–hole pairs are exploited to induce catalysis. Recently, powders of a metallic oxide (Sr1−xNbO3, 0.03<x<0.20) were reported to show competitive photocatalytic efficiencies under visible light, which was attributed to interband absorption. This discovery expanded the range of materials available for optimized performance as photocatalysts. Here we study epitaxial thin films of SrNbO3+δ and find that their bandgaps are ∼4.1 eV. Surprisingly, the carrier density of the conducting phase exceeds 1022 cm−3 and the carrier mobility is only 2.47 cm2 V−1 s−1. Contrary to earlier reports, the visible light absorption at 1.8 eV (∼688 nm) is due to the plasmon resonance, arising from the large carrier density. We propose that the hot electron and hole carriers excited via Landau damping (during the plasmon decay) are responsible for the photocatalytic property of this material under visible light irradiation.